Onychoscopy of nail lesions in dermatological disorders: A cross-sectional observational study - Aashna Sutaria; Devayani Pol; Kalyan Dalave; Mahendra S Deora; Yugal K Sharma; Chintal H Shah (Wolters Kluwer Medknow Publications, 2023)
Background: Nail disorders account for about 10% of all dermatological conditions. Onychoscopy is useful not only for their diagnosis but also for assessing severity/progression and monitoring the response to therapy. Aims and Objectives: Describing dermoscopic features of nail disorders in patients reporting to the dermatology OPD of our tertiary care hospital and recording the sociodemographic profiles thereof. Materials and Methods: This cross-sectional observational study was carried out on 176 patients with effect from August 2019 to August 2021. Results: Males (99; 56.25%) outnumbered females (77; 43.75%); males: female: 1.28: 1; their mean age was 35.8 years. Fingernails were affected more oftener (84.09%) than toenails (38.64%). Onychomycosis, the commonest (58;32.95%) condition, revealed findings of aurora borealis pattern (75.86%), subungual hyperkeratosis (72.41%), and onycholysis with jagged edges and spikes (68.97%). The next frequent (32;18.18%) condition was nail psoriasis which revealed pits (81.25%); onycholysis (62.5%) and dilated globose nail fold vessels on capillaroscopy (25%). Limitations: The small sample size proved inadequate for the evaluation of statistical significance in the less common conditions and the correlation of disease severity of many. Ideally, confirmatory diagnostic tests should have been done in every patient, as indicated. The magnification of our dermoscopy was 10X; 20- and 40X permit better capillaroscopy. Conclusions: Onychocopy can minimize the need for biopsy by highlighting subtle changes and helps narrow down the differentials. It is potentially a diagnostic test of choice in younger children. Our study helped to grade the severity of connective tissue disorders and establish the benignity of melanonychia. Photographic documentation facilitates record-keeping.